Unveiling the Significance of Surrogate Markers of Insulin Resistance in Metabolic Health Assessment - Najmunnissa; Kishorkumar M Guruswamy; Jadeppa Gowda; Swetha N Kempegowda; Akila Prashant; Suma M Nataraj (Indian Journal of Medical Biochemistry)
Recent years have evidenced an alarming increase in the incidence of diabetes mellitus (DM) and other metabolic disorders. Rapid urbanization and lifestyle changes have been the major factors for this increase. Early diagnosis is the key to better risk stratification and prompt management of these patients. Insulin resistance (IR) plays a pivotal role in the pathogenesis of various metabolic disorders. Assessing the IR in the initial stages would therefore help in early detection of patients who are susceptible to metabolic disorders. The hyperinsulinemic-euglycemic clamp technique has been the gold standard method for assessing IR. The major limitation of this technique is it is invasive and requires a specialized setup. Hence, identifying reliable surrogate markers for assessing IR is the need of the hour both in clinical and research settings. This review delves into the current knowledge of surrogate markers utilized to assess IR, providing a comprehensive overview of their strengths, limitations, and emerging trends. We explore commonly employed surrogate markers such as fasting insulin, homeostatic model assessment-insulin resistance (HOMA-IR), adiponectin, triglyceride-to-glucose index, etc. The search for accurate and cost-effective surrogate markers holds significant promise for early detection, risk stratification, and targeted interventions. This review aims to contribute to the existing knowledge on IR and highlight future directions in the quest for effective markers for IR.